The inner circle - Meltzer, Brad (Grand Central Pub., 2011)
A young archivist working in the National Archives and his childhood crush accidentally happen upon a priceless artifact--a 200-year-old dictionary that once belonged to George Washington--hidden inside a desk chair. Eager to discover why the President is hiding this important national treasure, the two soon find themselves entangled in a web of deception, conspiracy, and murder that will reveal the most well kept secret of the U.S. Presidency.